Common mental disorders and cause-specific disability retirement. Issue 3 (14th November 2014) - Lahelma, E; Pietiläinen, O; Rahkonen, O; Lallukka, T
Abstract : Objectives: Common mental disorders are prevalent among employees and may cause work disability. We aimed to examine the association between common mental disorders and disability retirement, with an emphasis on the severity of disorders and diagnostic causes for retirement. Methods: Our data were derived from the Helsinki Health Study cohort on the staff of the City of Helsinki, Finland. The baseline mail surveys were made in 2000–2002 among employees reaching ages 40, 45, 50, 55 and 60 in each year (n=8960, response rate 67%, 80% women). Disability retirement events from national registers (n=628) were followed up by the end of 2010 and linked to the baseline data. After exclusions, the number of participants was 6525. Common mental disorders were measured by the General Health Questionnaire 12-item version (GHQ-12). Covariates at baseline included sociodemographic, work-related and health-related factors. Hazard ratios (HR) and 95% CIs were calculated using Cox proportional hazards models. Results: Common mental disorders showed a graded association with disability retirement. For disability retirement due to any diagnostic cause, the fully adjusted HR for the GHQ-12 score 7–12 was 2.16, 95% CI 1.63 to 2.85. For disability retirement due to mental disorders the corresponding HR was 7.46, 95% CI 4.46 to 12.49. For disability retirement due to musculoskeletal diseases, the association was weaker and did not survive all adjustments. Conclusions: Common mental disorders are an important antecedent of disability retirement in general and due to mental disorders in particular. Successful measures against common mental disorders may prevent disability retirement due to mental disorders.